Antigenic and Molecular Detection of Adenoviruses from Sewage Water in Diyala Province – Iraq - Abdulqader Y. Hamad (Academic Science Journal, 2024)
Waterborne viral illnesses are still have public health in both developed and developing. Adenovirus one of the enteroviruses are widely circulated in the environment even in the absence of associated clinical conditions in the community. Adenoviruses are the second cause of gastroenteritis after rotavirus. as they are responsible for 5-9 % of gastroenteritis cases in children. The objectives of study antigenic and molecular detection of adenovirus from water samples collected from sewage water plants (SWP) and draining canals (DC) in Diyala city (Iraq). This study was conducted in Diyala province for the period from January 2022 to August 2022. A total of 50 water samples were collected from sewage water plants and draining canals in plastic containers Immunochromatographic Assay (ICA) technique was used for direct detection of adenoviruses antigens a for molecular detection, the water samples were firstly ultra – centrifuged and the then viral nucleic acid (NA) of adenovirus were extracted Polymerase Chain Reaction (PCR) adenoviruses RNAs concentration were measured. (Sacace Biotechnologies PCR kit) technique was used for viral NAs detection, analysis was done using the statistical packages for social science version (27) and P value was considered significant. The Result using the Immunochromatographic Assay (ICA) The total positivity rate of adenovirus in sewage water plants and draining canals 18 (36%), while the Polymerase Chain Reaction (PCR) technique found that the total positivity rate was 29 (58%). The high detection rate of adenoviruses found in sewage water plants and draining canals by both immunological and molecular techniques may reflect the high prevalence of the virus in the community and recreating the risks public health deterioration.